PERSUASI DIGITAL DAN ETIKA ISLAM: ANALISIS KONSEPTUAL IKLAN PINJAMAN ONLINE DAN PAYLATER DI MEDIA SOSIAL INDONESIA - Toni Priyanto (Bayani, 2026)
The rapid growth of financial technology (FinTech), particularly online lending and Buy Now, Pay Later (BNPL) services, has transformed digital financial services and marketing practices. Social media has become a key platform through which FinTech providers employ persuasive strategies to influence consumer perceptions and financial decisions. While these innovations promote financial inclusion and improve access to financing, persuasive messages emphasizing convenience, speed, and flexibility may also create information asymmetry and increase financial vulnerability, especially among consumers with limited financial literacy. This study examines digital persuasion in online lending and BNPL advertisements through the perspectives of bounded rationality, consumer protection, digital financial literacy, and Islamic ethics. Using a qualitative conceptual approach based on a literature review, the study finds that FinTech advertisements predominantly emphasize benefits and accessibility, while information regarding risks, costs, and financial obligations is often insufficiently disclosed. From an Islamic ethical perspective, digital financial advertising should adhere to the principles of sidq (truthfulness), bayan (transparency), adl (justice), amanah (accountability), the prohibition of gharar, and hifz al-mal (protection of wealth). As a conceptual contribution, this study proposes the Ethical Digital Finance Advertising Framework (EDFAF) and the Ethical Disclosure and Consumer Protection Index (EDCPI) to evaluate transparency, consumer protection, financial literacy support, and compliance with Islamic ethical principles in FinTech advertising.